Pembangunan rohani menurut perspektif tasawuf dan psikologi moden - Mostafa Kamal Mokhtar, (Penerbit Universiti Kebangsaan Malaysia, 2003)
In this article, the writer attempts to investigate comparatively the concept of human spiritual development proposed by Sufism and Modern Psychology. The writing is based on library research or documentary research, which is critically presented. The finding shows that even though both disciplines concern with human psyche, they clearly differ in conceptual understanding of human spiritual development as a resulf of embracing different ontological, epistemological and methodological concept of human being